Gender, sexuality and colonial modernities - Burton, Antoinette M. (Routledge, 1999)
Gender, Sexuality and Colonial Modernities considers the ways in which modernity was constructed, in all its incompleteness, through colonialism. Using a variety of archival resources and equally diverse methodologies, the authors trace modernity's unstable foundations in the slippages and ruptures of colonial gender and sexual politics. As a whole, the essays illustrate that modern colonial regimes are never self-evidently hegemonic, but are always in process - subject to disruption and contest - and never finally accomplished; and are therefore unfinished business.
Keywords: 1800-1899; approches et analyses; colonialisme; discipline; europe; fem1000; féminisme décolonial; histoire; occident; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; époque moderne; études postcoloniales

Feminism and nationalism in the Third World - Jayawardena, Kumari (Zed Books, 1986)
Un texte fondateur du féminisme transnational Depuis vingt-cinq ans, Feminism and Nationalism in the Third World est une introduction essentielle à l'histoire des mouvements de femmes en Asie et au Moyen-Orient à la fin du XIXe et au début du XXe siècle. Dans cette enquête engageante et bien documentée, Kumari Jayawardena présente le féminisme tel qu'il est né dans le Tiers-Monde, émergeant des luttes spécifiques des femmes luttant contre le pouvoir colonial, pour l'éducation ou le vote, pour la sécurité, et contre la pauvreté et les inégalités.
Keywords: 1800-1899; 1900-1999; afrique; approches et analyses; asie; fem1000; féminisme décolonial; féminisme transnational; inégalités; nationalisme; premier cycle; périodes historiques; régions géographiques; sud global; systèmes d'oppression; théories féministes